TINJAUAN PENOLOGI TERHADAP FENOMENA CYBERBULLYING DI MEDIA SOSIAL - Arief Tegar Prawira (ABISATYA DINAMIKA ISWARA, 2024)
The prevalence of cyberbullying behavior on social media platforms is increasing with the advancement of digital technology. The impact of cyberbullying is significant for individuals who are victimized, encompassing psychological and social aspects. This research aims to analyze the issue of cyberbullying from the perspective of criminal law (penology) by examining policies related to criminal sanctions and the effectiveness of law enforcement in Indonesia. The main focus of the analysis is the Law on Electronic Information and Transactions (UU ITE) and the Law of the Criminal Code (UU KUHP). The research method applied is a qualitative approach with normative juridical analysis of various laws and regulations, literature review, and case studies of cyberbullying that occur in Indonesia. The research results indicate that the existing regulatory framework has provided a solid legal basis for dealing with cyberbullying. However, implementation and law enforcement still face various obstacles. Recommendations from this research include strengthening regulations, increasing legal awareness in the community, and implementing models.